STUDY ABOUT THE PREVALENCE OF HIPERTENSION, DIABETES MELLITUS TYPE 2 AND PROSTAT CANCER IN PEOPLE WHO LIVE IN LAPA_ RIO DE JANEIRO. (Fiep Bulletin - online, 2014)
INTRODUCTION: The oldness is a historical, social and cultural phenomenon. Process that if does not summarize in demographic aspects, its complexity demands that it is studied by diverse discipline and under multiple angles. The aging alone emerged, while social phenomenon of high relevance, from our century, for the increase of the life expectancy and the advances in the area of the health, the basic sanitation, etc, (GOLDMAN, 2006). The presence of multiple diseases associates in the same person (frequent situation in the aged ones) increases the probability of incapacity for daily activities of life (AVD's) (BERGER, 1999). Narrow relation between aged incapacities and, and three known pathologies exists as the ones that more cause incapacities in the people with more than 65 years of age, are: artropatias, high blood pressure and cardiopathies. However, this knowledge is not significant in favored aged population groups less economically. OBJECTIVES: to inform to aged the region on High Systemic Pressure, Diabetes Mellitus and Prostate Cancer, to demonstrate to the importance of the partner in convincing its man to look the doctor and to carry through periodic preventive examinations and to verify the arterial blood pressure and measure the glycemic level of the volunteers. METHODOLOGY: the study if it characterized as pilot, description, of inquiry and participant. Pilot with 28 people counted in the meeting (4 men and 24 women) all with superior age the 65 years. The material to survey the pressure was: 3 devices of pressure of mark BD and 3 stethoscopes of the Littman marks. For the glicoteste the Acutrend_CGT device _ of the Roche. RESULTS: We identify during the application of the inquiry tool that, the majority of the people gifts was hipertensas of long date, making regular medicine use anti-hypertensives. However only it had a story of diabetes. How much á arterial pressure, only 6 people was with the pressure above of the considered value normal. The result of the glicoteste was the waited one, inside of the normal band (50 to the 139 mg/dL), with only two people being in the hyperglycemia band. CONCLUSIONS: With the carried through tests it was possible to only make a prompt survey of the pressure and glycemic level, not being able to serve as base diagnosis for that joined rejection of the normal band. In that she refers to the inventory we detect innumerable doubts concerning the subjects, and the search was great, or either, many people had demonstrated interest in more learning a little on these illnesses.
Keywords: Aging people; high blood pressure; diabetes mellitus type 2; Prostate Cancer